2005
DOI: 10.1167/iovs.05-0767
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Pathology, Altered Gene Expression, and Degeneration in Photoreceptors Impacted by Drusen

Abstract: Photoreceptors overlying and flanking drusen exhibit morphologic and biochemical signs of degeneration. The expression of synapse-associated proteins decreases in photoreceptor synaptic terminals, whereas the expression of stress-response proteins increases. Reductions in photoreceptor cell densities over, and flanking, drusen suggest that these degenerative effects eventually result in the death of photoreceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 40 publications
8
76
1
1
Order By: Relevance
“…It has been shown that photoreceptor cells in areas impacted by drusen exhibit morphologic and biochemical signs of degeneration, including decreased expression of synapse-associated proteins and increased expression of stress-response molecules. There are also drusen-associated reductions in photoreceptor cell densities, thus suggesting that degenerative changes in photoreceptors ultimately lead to cell death (151,152).…”
Section: Physiological Correlates Of Early Amdmentioning
confidence: 99%
“…It has been shown that photoreceptor cells in areas impacted by drusen exhibit morphologic and biochemical signs of degeneration, including decreased expression of synapse-associated proteins and increased expression of stress-response molecules. There are also drusen-associated reductions in photoreceptor cell densities, thus suggesting that degenerative changes in photoreceptors ultimately lead to cell death (151,152).…”
Section: Physiological Correlates Of Early Amdmentioning
confidence: 99%
“…In comparison, the AMD data and the current study most likely represent a degenerative process at different time scales: our data may represent the initial events whereas stress-response in diverse proteins may be a later event. Synaptic disassembly appears to arise early and is sustained for a long period (Johnson et al, 2005).…”
Section: Opsin Accumulation and Cyclic Illumination Promote Er-stressmentioning
confidence: 99%
“…Further, it was found that alpha crystallins accumulated in Bruch's membrane, choroidal connective tissue, and RPE to a greater degree in AMD than in normal non-AMD controls (Nakata et al, 2005, De et al, 2007. Expression of stress related proteins apolipoprotein E and αB crystallin increased in the photoreceptors over Drusen (Johnson et al, 2005).…”
Section: Introductionmentioning
confidence: 98%